EU administrative law - Craig, P. P. (Paul P.); Academy of European Law. (Oxford ; New York : Oxford University Press, 2006)
This is a legal evaluation of the ways in which the EU delivers policy. It assesses the role of law therein from a contextual and inter-disciplinary perspective and considers in-depth the principles of EU judicial review applicable to EU administration and that of the Member States.
Crisis, reform, and constitutionalization -- Centralized or direct community administration -- Shared management -- Comitology -- Agencies -- Open method of coordination -- Social partners -- Foundations -- Courts -- Access -- Process -- Competence and subsidiarity -- Law, fact, and discretion -- Rights -- Equality -- Legal certainty and legitimate expectations -- Proportionality I -- Proportionality II -- The precautionary principle -- Remedies I : the community -- Remedies II : member states -- The Ombudsman.
Includes index.
"Academy of European Law, European University Institute."
Includes bibliographical references and index.
Keywords: Administrative law -- European Union countries; Droit administratif -- Pays de l'Union européenne.